Economic Influence of Training in Brazilian Culture on Agricultural Exports from The Southern Macro-Region of Peru to Brazil by Land - Miguel PANEZ – BENDEZU (Communications of International Proceedings, 2022)
Knowing the culture from other countries is a key element to succeed in international business. In this sense, a way that local entrepreneurs can learn about culture of foreign countries is recurring to culture centers for online training in foreign language and culture. In this context, this study aims to determine how training in Brazilian culture influences agricultural exports from the southern macro-region of Peru to Brazil by land. The study is a mixed-method correlational design. The survey and the in-depth interview were used as techniques, and a questionnaire and an in-depth interview guide applied to seventeen experts in international trade, agricultural trade and regional development were used as instruments. Results indicate training in Brazilian culture influences agricultural exports and there is a positive correlation between training in Brazilian culture and agricultural exports from the southern macro-region of Peru to Brazil by land. In conclusion, Brazilian culture training influences agricultural exports from the southern macro-region of Peru to Brazil by land through the advertising. More specifically, a more degree of horizontal homogeneity of the client, enables farmers to increase their agricultural exports.
Keywords: agricultural trade; Brazilian culture; Brazilian culture training; degree of horizontal homogeneity of the client.